Moral Courage Among Clinical Nurses: A Comparison of Government Hospital and Private Hospital - Suarnianti; Indah Restika; Yusran Haskas (International Journal of Nursing and Health Services (IJNHS), 2021)
Strengthening moral courage is one of the effective ways to overcome moral distress that causes a lot of physical and emotional disturbance to a person, which affects their satisfaction with the profession. This study aimed to describe the moral courage in implementing the daily nursing practices of nurses in Indonesia. We applied the survey analytic research design in this. This research was conducted in 5 different locations, namely government and private hospitals in Makassar City, using multistage random sampling. The number of samples is 405 nurses. The results of the Moral courage nurses who work in Makassar city hospitals are at a moderate to the high level, and there is no difference in the level of moral courage nurses in government hospitals and private hospitals